Method for non-invasive assessment of the structure of a heart valve bioprosthesis - K. Yu. Klyshnikov; E. A. Ovcharenko; T. V. Glushkova; Yu. A. Kudryavtseva; L. S. Barbarash (Сибирский научный медицинский журнал)
Background. The study of explanted heart valve bioprostheses is a valuable source of information about the destructive processes in their components that develop as a result of prolonged contact with the recipient’s body. An analysis of the morphology, staging and degree of involvement of various valve prosthesis materials in the prevalence of pathological processes – calcification, mechanical damage, growth of the connective tissue capsule, is the basis for developing potential methods for increasing the service life of these products and reducing the risk of re-interventions. The aim of the study was to evaluate the potential of computed microtomography to analyze the internal structure of a biological prosthetic heart valve explanted due to dysfunction. Material and methods. In this work, we investigated the prevalence of pathological mineralization of the PeriCor bioprosthesis, explanted as a result of the developed dysfunction of the leaflet apparatus with a clinical picture of grade 2B prosthetic insufficiency. The material was described macroscopically, after which it was subjected to high-resolution computed microtomography. In the structure of the sample, X-ray dense areas of pathological mineralization were identified and described, and the volume of the material involved in calcification was assessed. Results. It was shown that the main pathological changes that led to prosthetic dysfunction were degenerative changes in the biomaterial with signs of calcification, thickening and rupture of the leaflets. It was quantitatively determined that the areas of radiologically dense inclusions (calcifications) occupy 11.1 % of the volume of the material. It has been established that the described areas are associated with the sheathing of the frame and with the elements of the suture material used in the production of this bioprosthesis. Conclusion. The method of non-destructive analysis of the internal structure of altered materials of a biological prosthesis studied in this work has demonstrated the possibility of а qualitative and quantitative assessment of areas of pathological mineralization, their distribution and connection with other processes leading to the development of prosthetic dysfunction. The method makes it possible to visualize macro- and microsites of calcification and can become a valuable tool to complement existing approaches to the study of explanted bioprostheses.